2013
DOI: 10.3390/nu5020608
|View full text |Cite
|
Sign up to set email alerts
|

Enteral and Parenteral Nutrition in the Perioperative Period: State of the Art

Abstract: Nutritional support of surgical and critically ill patients has undergone significant advances since 1936 when Studley demonstrated a direct relationship between pre-operative weight loss and operative mortality. The advent of total parenteral nutrition followed by the extraordinary progress in parenteral and enteral feedings, in addition to the increased knowledge of cellular biology and biochemistry, have allowed clinicians to treat malnutrition and improve surgical patient’s outcomes. We reviewed the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 61 publications
(138 reference statements)
1
71
0
3
Order By: Relevance
“…We did not use endoscopically placed gastrostomy or combined gastrostomy-jejunal tubes. Although we did not perform any cost estimate analysis of parenteral vs enteral feeding in this cohort, it is well established that enteral nutrition is less costly than TPN[24,25]. Data from Mack et al[22], as well as cost-analysis modeling[26], demonstrated that costs for patients treated with a gastrojejunostomy tube were less than those for patients treated without a gastrojejunostomy, even though 100% of patients in the gastrojejunostomy group received nutritional supplementation compared with only 20% to 40% of the patients in the group treated by more standard methods[22,26].…”
Section: Discussionmentioning
confidence: 99%
“…We did not use endoscopically placed gastrostomy or combined gastrostomy-jejunal tubes. Although we did not perform any cost estimate analysis of parenteral vs enteral feeding in this cohort, it is well established that enteral nutrition is less costly than TPN[24,25]. Data from Mack et al[22], as well as cost-analysis modeling[26], demonstrated that costs for patients treated with a gastrojejunostomy tube were less than those for patients treated without a gastrojejunostomy, even though 100% of patients in the gastrojejunostomy group received nutritional supplementation compared with only 20% to 40% of the patients in the group treated by more standard methods[22,26].…”
Section: Discussionmentioning
confidence: 99%
“…70 Previous economic analyses report cost savings with the use of the enteral route, rather than the parenteral route, in critically ill patients. 3,75,76 However, these results need to be interpreted with caution, as no incremental cost-effectiveness results were provided. A few economic analyses performed only cost-minimisation analysis because there were no differences in outcome between the parenteral and enteral routes.…”
Section: Results In Contextmentioning
confidence: 99%
“…More than that, the composition of free intracellular amino acid and α-ketoacid pools in body cells do not seem to be arbitrary in any direction, but may rather represent a relevant metabolic correlate, a quasi-immunonutritional metabolic fingerprint, for the underlying functions [24]- [26]. It is thus not surprising that scientific interest here also focused on the possibility to use selected amino-or ketoacids as part of a "standard" diet therapeutically [27]- [29]. However, many questions are unfortunately here still unclear.…”
Section: Discussionmentioning
confidence: 99%